TRENDS IN ISLAMIC FEMINIST EXEGESIS: A LITERATURE REVIEW - Ulvah Nur'aeni; binti Kamaruddin, Kasimah (Department Islamic Education, Faculty of Education and Teacher Traning, Universitas Islam Bandung, 2025)
This literature review examines contemporary trends in Islamic feminist thought from 2020 to 2025, focusing on new feminist readings of the Qur'an, the reconstruction of gender exegesis in global Islamic feminist movements, thematic reinterpretations of women-related verses, and critical examinations of women's marginalization in Qur'anic translation and transmission. The study employs a qualitative systematic review of 12 Scopus-indexed articles, utilizing thematic analysis to identify recurring concepts, methodological patterns, and interpretive frameworks. The findings reveal a growing methodological sophistication in Islamic feminist scholarship, characterized by inclusive interpretive models that integrate socio-historical context, women's lived experiences, and contemporary gender issues. The study also highlights the efforts of Muslim feminists in various countries to defend women's rights, roles, and mobility through distinctive and effective movements that reinterpret Qur'anic verses traditionally understood through gender-biased lenses. Furthermore, the review underscores the importance of thematic reinterpretation of women-related verses, which challenges patriarchal bias in classical commentaries, foregrounds egalitarian principles, and exposes gender injustice in contemporary contexts. Finally, the study critically examines various forms of women's marginalization in the religious domain, including gender-biased interpretations, limited recognition of women's roles in Qur'anic transmission, and gender bias in Qur'anic translations. The article concludes that contemporary Islamic feminist discourse is marked by increasing global interconnectedness and a shift toward interpretations that emphasize ethical equality and gender justice as intrinsic to the Qur'anic worldview, while also highlighting the need for more inclusive spaces for women in the production and transmission of religious knowledge.